2019
DOI: 10.1111/appy.12379
|View full text |Cite
|
Sign up to set email alerts
|

Seeking for potential pathogenic genes of major depressive disorder in the Gene Expression Omnibus database

Abstract: Introduction: Major depressive disorder (MDD) is one of the most common mental disorders worldwide. The aim of this study was to identify potential pathological genes in MDD. Methods: We searched and downloaded gene expression data from the Gene Expression Omnibus database to identify differentially expressed genes (DEGs) in MDD. Then, Kyoto Encyclopedia of Genes and Genomes pathway, Gene Ontology analysis, and protein-protein interaction (PPI) network were applied to investigate the biological function of ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…The Adapter Protein 2 (AP2) complex targets specific membrane-associated proteins for clathrin-mediated endocytosis via its α, β, σ, and µ subunits (Traub and Bonifacino, 2013), and these subunits have been linked to diverse aspects of clinically-relevant behavioral control (Chen et al, 2013; Chinoy et al, 2017; Helbig et al, 2019; Bonnycastle et al, 2021). Expression levels of the AP2β subunit ( AP2B1 ) are altered in the brains of individuals with schizophrenia and major depressive disorder, and AP2 subunit expression is reduced in the brains of untreated individuals with bipolar disorder (Chen et al, 2013; Föcking et al, 2015; Forero et al, 2017; Feng et al, 2020). Mutations disrupting the AP2µ subunit ( AP2M1 ) are associated with severe disruption in cognition and behavior in humans (Helbig et al, 2019), while mutations in the AP2σ subunit ( AP2S1 ) are associated with behavior changes characteristic of autism spectrum disorders, attention hyperactivity disorder, learning disorders, and cognitive dysfunction (Hannan et al, 2015; Chinoy et al, 2017; Szalat et al, 2017; Aashiq et al, 2020; Satterstrom et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Adapter Protein 2 (AP2) complex targets specific membrane-associated proteins for clathrin-mediated endocytosis via its α, β, σ, and µ subunits (Traub and Bonifacino, 2013), and these subunits have been linked to diverse aspects of clinically-relevant behavioral control (Chen et al, 2013; Chinoy et al, 2017; Helbig et al, 2019; Bonnycastle et al, 2021). Expression levels of the AP2β subunit ( AP2B1 ) are altered in the brains of individuals with schizophrenia and major depressive disorder, and AP2 subunit expression is reduced in the brains of untreated individuals with bipolar disorder (Chen et al, 2013; Föcking et al, 2015; Forero et al, 2017; Feng et al, 2020). Mutations disrupting the AP2µ subunit ( AP2M1 ) are associated with severe disruption in cognition and behavior in humans (Helbig et al, 2019), while mutations in the AP2σ subunit ( AP2S1 ) are associated with behavior changes characteristic of autism spectrum disorders, attention hyperactivity disorder, learning disorders, and cognitive dysfunction (Hannan et al, 2015; Chinoy et al, 2017; Szalat et al, 2017; Aashiq et al, 2020; Satterstrom et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results of our screening were also validated in other studies. On the one hand, through gene database analysis, Feng et al identified AP2B1 as a potential therapeutic target for major depressive disorder [26]. At the same time, fluoxetine treatment can significantly increase the expression of AP2B1 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the pathological consequences of AP2B1 mutation are similar to those of the AP2α subunit mutation and has been shown to have various effects in neural tissue. In fact, AP2B1 affects dendrite cell morphology by controlling the mTOR pathway [ 97 ] through its action as a biosignature upon antidepressant treatment [ 98 ], binding to Dynamin-1, and triggering the process of autophagy, which inhibits dementia [ 99 ] and is putatively linked to depressive disorder [ 100 ]. AP2B1 is also linked to Alzheimer’s disease [ 101 ], which explains the importance of the AP2 complex in controlling autophagy and lysosomal protein degradation that regulate this neuronal degenerative disease.…”
Section: Ap2 Complexmentioning
confidence: 99%